2008
DOI: 10.1111/j.1365-2117.2007.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal modelling of magmatic intrusions in the Gjallar Ridge, Norwegian Sea: implications for vitrinite reflectance and hydrocarbon maturation

Abstract: Extensive magmatic activity took place in the VÖring Basin, o¡shore Norway, related to the Early Cenozoic rifting.The break-up of the North-Atlantic at the Palaeocene^Eocene transition induced strong volcanism.There are numerous magmatic sills below 3 km depth in the area.They are predominantly layer parallel and thin compared with their lateral extent. Igneous intrusions, sills and dykes a¡ected the temperature history, and thus need to be taken into account in petroleum prospect analysis.We have calculated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 30 publications
1
53
0
1
Order By: Relevance
“…Modeling provided Data provided Intrusion thickness Normalized aureole Lithology of host-rock Barker and Bone (1995) V b -Da 2.2 m $5% D High grade limestone Barker et al (1998) T-F-L C V 0.06 -40 m 30-150% a D Clay/sediments Bishop and Abbott (1995) T V-TOC-RE-GC 0.3-3.0 m 30-70% a D Shale/silty shale Brown et al (1994) T-Ro V 40-60 m 150% a S Shale/limestone Bostick and Pawlewicz (1984) V 3.6-10.4 m 75-100% a D Shale/limestone Clayton and Bostick (1986) V-RE-GC-Da 1.3 m $50% a D Siltstone Cooper et al (2007) V-TOC-Da 0.15-1.8 m 75-110% a S/D Coal/black shale Delaney (1982) T Drits et al (2007) Mi 0.5-80 m $75% b S Mudstone Dutrow et al (2001) T-F-R TOC-Da 11 m 35-55% b D Carbonate/siltstone Finkelman et al (1998) V-RE-El-Mi 1.5 m $35% a D Coal/coke Fjeldskaar et al (2008) T-Ro V 118.5 m $150% c S Silt/shale/sandstone Galushkin (1997) T-F-L C -L D -Ro V 0.9-118.5 m 55-170% a S/D Black shale/silt George (1992) V-RE-GC-Da 3.5 m $70% a D Silt/oil shale Golab et al (2007) Mi Hanson and Barton (1989) T-L C -L D D Jaeger (1959) T-F-L V 100% c Kjeldstad et al (2003) T-F-P-Ro Litvinovski et al (1990) T-L M -P 500 m >>10% b D Clay/pumice Mastalerz et al (2009) V-Da >1.2 m $50% a D Coal Meyers and Simoneit (1999) TOC-RE-Da 1.5 m $60% b S Coal Othman et al (2001) V-RE-GC 0.40-15.7 m S Mudstone Perregaard and Schiener (1979) V-GC 4.5 m $50% a D Shale Peters et al (1983) V-RE-GC 0.2-15 m 50-70% a S Black shale Polyansky and Reverdatto (2006) T-L M -F-R 280 m 10-70% c S Sand/siltstone Raymond and Murchison (1988) V 50-118.5 m $100-200% a S Shale/silt/limestone Rodriguez Monreal et al (2009) T-Ro-HC V-RE-GC 110-600 m 50-100% a S Black shale Santos et al (2009) T Mi-El 13 m $90% b S Carbonate/ black shale Saxby and Stephenson (1987) TOC-GC-Da 3 m $50% b S Oil shale Simoneit et al (1978Simoneit et al ( , 1981 V-TOC-GC-Da 0.2-15 m 40-50% a ...…”
Section: Referencesmentioning
confidence: 99%
“…Modeling provided Data provided Intrusion thickness Normalized aureole Lithology of host-rock Barker and Bone (1995) V b -Da 2.2 m $5% D High grade limestone Barker et al (1998) T-F-L C V 0.06 -40 m 30-150% a D Clay/sediments Bishop and Abbott (1995) T V-TOC-RE-GC 0.3-3.0 m 30-70% a D Shale/silty shale Brown et al (1994) T-Ro V 40-60 m 150% a S Shale/limestone Bostick and Pawlewicz (1984) V 3.6-10.4 m 75-100% a D Shale/limestone Clayton and Bostick (1986) V-RE-GC-Da 1.3 m $50% a D Siltstone Cooper et al (2007) V-TOC-Da 0.15-1.8 m 75-110% a S/D Coal/black shale Delaney (1982) T Drits et al (2007) Mi 0.5-80 m $75% b S Mudstone Dutrow et al (2001) T-F-R TOC-Da 11 m 35-55% b D Carbonate/siltstone Finkelman et al (1998) V-RE-El-Mi 1.5 m $35% a D Coal/coke Fjeldskaar et al (2008) T-Ro V 118.5 m $150% c S Silt/shale/sandstone Galushkin (1997) T-F-L C -L D -Ro V 0.9-118.5 m 55-170% a S/D Black shale/silt George (1992) V-RE-GC-Da 3.5 m $70% a D Silt/oil shale Golab et al (2007) Mi Hanson and Barton (1989) T-L C -L D D Jaeger (1959) T-F-L V 100% c Kjeldstad et al (2003) T-F-P-Ro Litvinovski et al (1990) T-L M -P 500 m >>10% b D Clay/pumice Mastalerz et al (2009) V-Da >1.2 m $50% a D Coal Meyers and Simoneit (1999) TOC-RE-Da 1.5 m $60% b S Coal Othman et al (2001) V-RE-GC 0.40-15.7 m S Mudstone Perregaard and Schiener (1979) V-GC 4.5 m $50% a D Shale Peters et al (1983) V-RE-GC 0.2-15 m 50-70% a S Black shale Polyansky and Reverdatto (2006) T-L M -F-R 280 m 10-70% c S Sand/siltstone Raymond and Murchison (1988) V 50-118.5 m $100-200% a S Shale/silt/limestone Rodriguez Monreal et al (2009) T-Ro-HC V-RE-GC 110-600 m 50-100% a S Black shale Santos et al (2009) T Mi-El 13 m $90% b S Carbonate/ black shale Saxby and Stephenson (1987) TOC-GC-Da 3 m $50% b S Oil shale Simoneit et al (1978Simoneit et al ( , 1981 V-TOC-GC-Da 0.2-15 m 40-50% a ...…”
Section: Referencesmentioning
confidence: 99%
“…Vitrinite maturation models use the EASY%Ro vitrinite reflectance model developed by Sweeney & Burnham (1990). Our model is described in detail in Fjeldskaar et al (2008). The calculated vitrinite reflectance for the various thermal conductivity models is shown in Figure 20.…”
Section: Vitrinite Reflectancementioning
confidence: 99%
“…(cf. Fjeldskaar et al 2008). The temperature regime was determined for each of these 14 time slices of the geohistory.…”
Section: Modelling Proceduresmentioning
confidence: 99%
“…Fjeldskaar et al [10] presented case studies of the thermal impact of sill intrusions in the sediments in the Vøring Basin, and Fjeldskaar et al [9,11] have shown case studies of temperature transients in the sedimentary basin from magmatic underplating. The basis for their study is a backward kinematic modelling tool, creating areabalanced cross-sections in environments with normal or reverse faults.…”
Section: Introductionmentioning
confidence: 97%